Effects of Formaldehyde-Treated Feed on Rumen Metabolism and Blood Biochemistry in Lambs: A Review - Chauhan, D S; Tanpure, Mahesh Uttam; Jeet, Indra; Chattopadhyay, Dipanwita; Odoh, Chidubem Hillary; Ganai, Imran Ahmad; Srivastava, Priya; Devi, Huirem Diana; Khurshid, Ibraq (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This review evaluates the impact of formaldehyde treatment on feed for lambs, focusing on its effects on rumen metabolism and blood biochemical indicators. Formaldehyde is commonly used as a feed additive to improve nutritional efficiency and preserve feed quality. This review synthesizes data from various studies to assess how formaldehyde-treated feed influences rumen fermentation parameters, including volatile fatty acid (VFA) production, rumen pH, and microbial activity. Additionally, the review examines the effects of formaldehyde treatment on key blood biochemical markers such as glucose, urea nitrogen, and liver enzymes. Studies indicate that formaldehyde treatment can enhance the stability and digestibility of feed, potentially improving nutrient utilization and overall animal performance. The preservation of protein and reduction in feed spoilage are highlighted as significant benefits, contributing to more consistent rumen function and metabolic efficiency. However, the impact on rumen microbial populations and VFA profiles shows mixed results, with some studies reporting improved microbial efficiency and others noting minimal changes. The review also discusses potential adverse effects, including alterations in blood biochemical parameters. While formaldehyde treatment generally maintains or improves key indicators like blood glucose and protein levels, excessive use may lead to concerns such as elevated urea nitrogen levels and potential liver enzyme disruptions, the review concludes that formaldehyde-treated feed can be a valuable tool in optimizing feed efficiency and lamb health, provided it is used judiciously. Future research is recommended to further elucidate the long-term effects on rumen microbiota and metabolic processes, ensuring balanced benefits without compromising animal welfare.